Investigating the association between population density and travel patterns in Indian cities—An analysis of 2011 census data. (May 2020) - Goel, Rahul; Mohan, Dinesh
Abstract: Many transport planners consider urban population density to be a significant determinant of travel behaviour. Much of the evidence for this comes from research in low-density, high-income settings. The 2011 Census of India reported mode of travel to work and distance for the first time. We have used these data to investigate the effect of urban density on commute travel patterns at city-level for Indian cities. In addition, we investigated the relationship between travel behaviour and other city-level variables. Using regression, we found almost no independent effect of density on the mode share of walk, cycle, motorised two-wheelers, cars and public transport, after controlling for population and income levels for the cities. Further, it appears that once density levels are greater than 80 persons per hectare (pph), other factors become more important in determining travel patterns in cities. This evidence has significant implications for urban planning and transport policy in Indian cities and for many other low- and middle-income cities where average density tends to be higher than 80 pph. For these cities, growth in the use of sustainable transport may not depend on further densification of already dense cities, but on details of how neighbourhoods and streets are designed. Highlights: Census in India reported travel mode and distance of work trips for the first time. Most Indian cities have higher density than the densest cities in the high-income countries. Large changes in population density have only negligent effect on travel patterns. Population size and city-level income are more important determinants of travel behavior.